Genetic Analysis in Japanese Kindreds of Congenital Type I Antithrombin Deficiency Causing Thrombosis - Nakahara, Yoshifumi; Tsuji, Hajime; Nakagawa, Katsumi; Masuda, Haruchika; Kitamura, Hidetsugu; Nishimura, Hiromi; Kasahara, Teruhisa; Sugano, Tatsuya; Sawada, Shohei; Nakagawa, Masao (Thrombosis and Haemostasis, 1997)
We have identified two novel minor deletions (case 1; -TA or -AT at nucleotide 9831-3 in exon 5 and case 2; -A at nucleotide 7640-1 in exon 4), one novel nonsense mutation (case 3; TAT to TAA at nucleotide 7491 in exon 4), and one recurrent nonsense mutation (case 4; CGA to TGA at nucleotide 5381 in exon 3A) in Japanease kindreds with congenital type I antithrombin deficiency. The deletion detected in case 1 represented a symmetric element (CTCTGTCTC) and possessed a direct repeat (CTCTATGTCTC). The deletion in case 2 was recognized in a consensus sequence (TGAAT) and possessed a direct repeat (GATGAA). The nonsense mutation in case 3 formed a palindrome (CCGTTAACGG) and that in case 4 was caused hy a CpG dinucleotide mutation. These results confirm that the mutations of congenital type I antithrombin deficiency are not random events but are influenced strongly by DNA sequences.